What drives bank coverage ratios: Evidence from the euro area - Lucia Alessi; Brunella Bruno; Elena Carletti; Katja Neugebauer (Publications Office of the European Union, 2019)
We analyse micro and macro drivers of coverage ratios in a cross-country sample of euro area banks. Among the former, we find that coverage ratios increase with the reliance on deposit funding and when asset quality is very poor. Among the latter, coverage ratios increase with GDP growth and with more stringent supervision and macro-prudential policies, as well as with deeper NPL secondary markets. Finally, we find evidence of peer imitation behaviour, as banks with below country average coverage ratios increase coverage ratios to catch up with their peers. As for the prevalent mechanism, banks tend to enhance coverage ratios primarily by increasing loan loss reserves rather than by resolving NPLs.
Keywords: G21; G28; M41; 330; loan loss reserves; non-performing loans; loan loss coverage